2012
DOI: 10.3390/buildings2030245
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Cradle-to-Gate Life Cycle Assessment of Mid-Rise Office Building Construction Alternatives: Laminated Timber or Reinforced Concrete

Abstract: The objective of this project was to quantify and compare the environmental impacts associated with alternative designs for a typical North American mid-rise office building. Two scenarios were considered; a traditional cast-in-place, reinforced concrete frame and a laminated timber hybrid design, which utilized engineered wood products (cross-laminated timber (CLT) and glulam). The boundary of the quantitative analysis was cradle-to-construction site gate and encompassed the structural support system and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(116 citation statements)
references
References 22 publications
2
91
0
1
Order By: Relevance
“…Although there have been some simple methods developed for architects to carry out fast LCA, such as that proposed by Hollberg and Ruth [26], building construction is a complicated process and often not all the details in all the locations could be obtained to put into the analysis. For example, some analyses only include the materialisation process [27]. It is therefore essential to define the boundary of the analyses when carrying out LCA or LCEA, Figure 7 depicts the boundary of analyses in this study.…”
Section: The Frameworkmentioning
confidence: 99%
“…Although there have been some simple methods developed for architects to carry out fast LCA, such as that proposed by Hollberg and Ruth [26], building construction is a complicated process and often not all the details in all the locations could be obtained to put into the analysis. For example, some analyses only include the materialisation process [27]. It is therefore essential to define the boundary of the analyses when carrying out LCA or LCEA, Figure 7 depicts the boundary of analyses in this study.…”
Section: The Frameworkmentioning
confidence: 99%
“…Another limitation in the current body of literature is that even of the studies that have included multiple impact categories, only a very few concentrate on the early life cycle or the embodied and construction phase emissions of buildings (Thormark et al 2000, Robertson et al 2012, Dong and Ng 2015. The other studies have focused mainly on comparing the relative importance of the different life cycle phases (Junnila 2004, Junnila and Horvath 2003, Guggemos and Horvath 2005, Junnila et al 2006, Kofoworola and Gheewala 2008, Passer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is considered as a typical concrete mix for multi-storey buildings within Australia (Cement Australia 2015). The fly ash mix can be left variable as it has been found that a simple change by adding 5% more fly ash has minimal effect on embodied energy of the concrete (Robertson, Lam & Cole 2012). The CLT panels are assumed to be supplied from KLH in Austria.…”
Section: Floor Design Assumptionsmentioning
confidence: 99%
“…A study undertaken by Robertson et al (2012) has revealed that timber design has over five times more feedstock energy than a concrete design scenario. Feedstock energy is the easily accessible potential energy contained in renewable fuel sources that can be used to form another fuel or energy product.…”
Section: Demolition and End Of Life Scenariosmentioning
confidence: 99%
See 1 more Smart Citation